The Role of Academic Stress on Self-Efficacy Among Final Semester Student Athletes - Hasanuddin; Gamar Al Haddar; Petra Heidler; Mohammed Aljuaid; Syed Haider Ali Shah, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Academic stress and self-efficacy significantly impact the academic performance of student athletes. It is crucial to comprehend the connection between these two factors to develop successful interventions that enhance the well-being and performance of student athletes. Examining how academic stress affects self-efficacy in a group of 270 senior student athletes across various academic fields was the focus of this research. The data collected from the respondents was analysed using simple linear regression analysis and SPSS software. The findings indicated a notable inverse relationship between academic stress and self-efficacy. This discovery highlights the significance of handling stress in academia to boost the self-belief of student athletes. The results make a significant contribution to the field of educational psychology by exploring the connection between stress and self-efficacy in students, offering key insights for interventions to reduce stress and enhance self-efficacy among student athletes.